TRP channels, the missing link for Ca2+ tuning by a unicellular eukaryotic parasite?. (September 2021) - Theopold, Ulrich; Barragan, Antonio
Abstract: Sensing and responding to changes in the cellular environments are essential for the diverse family of Apicomplexan parasites, which undergo complex life cycles comprised of both extracellular and obligate intracellular stages. Despite evidence of paramount roles for Ca 2+, the molecular players behind how parasites sense Ca 2+ and initiate Ca 2+ signaling cascades have remained enigmatic. In a recent publication, Marquez-Nogueras et al., identify a transient receptor potential (TRP)-like channel in Toxoplasma gondii and show its implication in the crucial processes of parasite invasion and egress from host cells.